THE IMPACT OF THE DIGITAL ENVIRONMENT ON THE STRUCTURE AND FUNCTIONING OF SYNTACTIC UNITS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the impact of the digital communicative environment on the syntactic structure of the modern Russian language. It analyzes the structural and functional transformations of syntactic units in the context of Internet-mediated communication, including the tendency toward syntactic compression and simplification, the increasing use of parcellation, ellipsis, and nominative constructions, the fragmentation of utterances into separate messages, changes in the functions of punctuation, and the emergence of polycode syntactic markers. Special attention is paid to the hypertextual organization of texts and the genre-specific nature of the observed processes. The study concludes that the digital environment does not destroy the syntactic system but rather restructures it, forming new norms of written colloquial speech. Prospects for further comparative studies of these processes are also outlined.